(untitled) (Papeles, 2025)
This paper aims to shed light on the institutionalization of the profession in Santiago del Estero through an analysis of historical processes for reconstructing the history of Social Work. It draws on the work of local authors who provide diverse insights into the political, economic, institutional, and professional processes of Social Work in Santiago del Estero. In recent years, members of the professional collective have been conducting research from the historical-critical perspective on the history of Social Work in the province of Santiago del Estero, especially it is pertinent to highlight the team of History and Foundations of Social Work of the first year of the Bachelor’s Degree in Work at the Faculty of Humanities, Social Sciences and Health, which also aims to provide a continuity in the chronology of dates studied so far identified the institutionalization of the profession in the province.